Blinding Trachoma: Systematic Review of Rates and Risk Factors for Progressive Disease. - Athumani M Ramadhani; Tamsyn Derrick; Martin J Holland; Matthew J Burton (PLoS Neglected Tropical Diseases)
Background Sight loss from trachoma is the end result of a scarring disease process starting in early childhood and characterised by repeated episodes of conjunctival inflammation (active trachoma). Subsequently, the conjunctiva becomes scarred, causing the eyelashes to turn inwards and scratch the cornea (trichiasis), damaging the corneal surface and leading to corneal opacification and visual impairment. It is thought that this process is initiated and driven by repeated infection with Chlamydia trachomatis. We review published longitudinal studies to re-examine the disease process, its progression rates and risk factors. Methodology/principal findings We searched PubMed for studies presenting incidence and progression data for the different stages of trachoma natural history. We only included studies reporting longitudinal data and identified 11 publications meeting this criterion. The studies were very heterogeneous in design, disease stage, duration, size and location, precluding meta-analysis. Severe conjunctival inflammation was consistently associated with incident and progressive scarring in five studies in which this was examined. One study reported an association between C. trachomatis infection and incident scarring. No studies have yet demonstrated an association between C. trachomatis infection and progressive scarring. Several studies conducted in regions with low prevalence active disease and C. trachomatis infection found evidence of on-going scarring progression. Conclusions/significance Overall, there are few longitudinal studies that provide estimates of progression rates and risk factors, reflecting the challenges of conducting such studies. Our understanding of this disease process and the long-term impact of control measures is partial. Intense conjunctival inflammation was consistently associated with scarring, however, direct evidence demonstrating an association between C. trachomatis and progression is limited. This suggests that on-going chlamydial reinfection may not be mandatory for progression of established scarring, indicating that sight threatening trichiasis may continue to evolve in older people in formerly endemic populations, that will require service provision for years after active disease is controlled.